2011
DOI: 10.1001/archophthalmol.2010.323
|View full text |Cite
|
Sign up to set email alerts
|

Shared Genetic Determinants of Axial Length and Height in Children

Abstract: Methods: Study participants were recruited from the Guangzhou Twin Registry. Axial length was measured using partial coherence laser interferometry. Height was measured with the participants standing without shoes. We computed twin pairwise correlations and cross-twin crosstrait correlations between AL and height for monozygotic and dizygotic twins and performed model-fitting analyses using a multivariate Cholesky model. The right eye was arbitrarily selected to represent AL of participants. Results: Five hund… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
44
2

Year Published

2013
2013
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 44 publications
(50 citation statements)
references
References 28 publications
4
44
2
Order By: Relevance
“…By comparing growth trajectories in children with the stature of their parents, Botton et al 40 have shown that this relatively straightforward scenario hides a complex interplay of maternal and paternal genetic, epigenetic or shared environment effects, alternating in their impact at different stages of childhood. Our findings regarding the growth trajectories of height (and weight) and ocular component dimensions at age 15, were in accordance with the consensus from previous work [13][14][15][16][17][18][19]25 , namely, that tall individuals tend to have larger eyes (a longer axial length and a flatter cornea). Again, however, the magnitude of these associations in the ALSPAC cohort was modest -explaining at most a few percent of the natural variation in AXL and RCC at age 15 years.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…By comparing growth trajectories in children with the stature of their parents, Botton et al 40 have shown that this relatively straightforward scenario hides a complex interplay of maternal and paternal genetic, epigenetic or shared environment effects, alternating in their impact at different stages of childhood. Our findings regarding the growth trajectories of height (and weight) and ocular component dimensions at age 15, were in accordance with the consensus from previous work [13][14][15][16][17][18][19]25 , namely, that tall individuals tend to have larger eyes (a longer axial length and a flatter cornea). Again, however, the magnitude of these associations in the ALSPAC cohort was modest -explaining at most a few percent of the natural variation in AXL and RCC at age 15 years.…”
Section: Discussionsupporting
confidence: 92%
“…This suggests that early growth is more important in determining RCC in young adulthood than is the case for AXL, which is consistent with the virtual cessation in RCC growth seen in both cross-sectional and longitudinal studies after the first few years of life, compared to the continued elongation of the globe 10,14,55,56 . The association between stature and eye size has led to the suggestion that genetic variants known to influence height might also influence axial length 25,56,57 . However, we found no evidence that a group of common SNPs that explain ~10% of the variation in adult height 27 and 5-6% of the variation in height by age 10 years 41 was predictive of AXL.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The phenotypic correlations between height and corneal curvature (q p ¼ 0.22; P < 0.001) and between height and axial length (q p ¼ 0.20; P < 0.001) were less than half those between the two ocular traits themselves, and the corresponding lower-bound genetic correlation estimates were also approximately 50% lower (q g < 0.42, SE ¼ 0.20-0.25, P > 0.1). The bivariate heritability of 89% for axial length and height, reported in a recent analysis in young Chinese twins by Zhang et al, 12 suggests a strong genetic involvement in the coregulation of these traits. However, from the Cholesky path model factor loadings presented by Zhang et al, we calculated a genetic correlation between axial length and height q g ¼ 0.19 for their twin sample (using the formula q g ¼ a 21 /=h 2 ; ¼ 0.18/=0.92; where a 21 is the loading of common additive genetic effects on axial length and height, and h 2 is the heritability of height).…”
Section: Figurementioning
confidence: 84%
“…In a recent twin study, the bivariate heritability (the proportion of the phenotypic correlation that is mediated by a correlation at the genetic level 11 ) for axial length and height was calculated to be 89% by Cholesky modeling. 12 In emmetropic chickens, 3 the phenotypic and genetic correlations between body size and axial length were both~0.5. Past studies into the role of genetic and nongenetic influences on ocular component dimensions have relied on studies of related individuals.…”
mentioning
confidence: 99%